Access to production information among citrus farmers in Atisbo Local Government Area of Oyo State (2007)
The study was conducted to determine the level of awareness, access and utilization of sixteen, Citrus production by citrus farmers in ATISBO Local Government Area of Oyo State. Structured interview schedule were administered on sixty citrus farmers who were purposively selected from six communities. Descriptive statistics such as frequency distribution, percentage and rating were used to analyse the data. Ninety eight point three (98.3%) of the respondents were male and 85 percent (85%) were married. The main source of information was village extension agents and contact farmers as indicated by 46.7 percent and 41.7 percent of respondents. Sixty eight percent of the farmers experience low yield of citrus. Level of information awareness, access and utilization of citrus farm practices was low. That is 63.3, 58.86 and 50 percent of the respondents had low scores respectively. The extension agents have been encouraged to release to farmers necessary information that could lead to high citrus production in the area.